The Ton System, an ABC Transporter, and a Universally Conserved GTPase Are Involved in Iron Utilization by Brucella melitensis 16M - Danese, Isabelle (American Society for Microbiology, 2004)
Brucella spp. are gram-negative intracellular facultative pathogens that are known to produce 2,3-dihydroxybenzoic acid (DHBA), a catechol siderophore that is essential for full virulence in the natural host. The mechanism of DHBA entry into Brucella and other gram-negative bacteria is poorly understood. Using mini-Tn5Kmcat mutagenesis, we created a transposon library of Brucella melitensis 16M and isolated 32 mutants with a defect in iron acquisition or assimilation. Three of these transposon mutants are deficient in utilization of DHBA. Analysis of these three mutants indicated that the ExbB, DstC, and DugA proteins are required for optimal assimilation of DHBA and/or citrate. ExbB is part of the Ton complex, and DstC is a permease homologue of an iron(III) ABC transporter; in gram-negative bacteria these two complexes are involved in the uptake of iron through the outer and inner membranes, respectively. DugA is a new partner in iron utilization that exhibits homology with the bacterial conserved GTPase YchF. Based on this homology, DugA could have a putative regulatory function in iron assimilation in Brucella. None of the three mutants was attenuated in cellular models or in the mouse model of infection, which is consistent with the previous suggestion that DHBA utilization is not required in these models.